2014
DOI: 10.1155/2014/169130
|View full text |Cite
|
Sign up to set email alerts
|

Honey: A Potential Therapeutic Agent for Managing Diabetic Wounds

Abstract: Diabetic wounds are unlike typical wounds in that they are slower to heal, making treatment with conventional topical medications an uphill process. Among several different alternative therapies, honey is an effective choice because it provides comparatively rapid wound healing. Although honey has been used as an alternative medicine for wound healing since ancient times, the application of honey to diabetic wounds has only recently been revived. Because honey has some unique natural features as a wound healer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 157 publications
(136 reference statements)
0
95
0
4
Order By: Relevance
“…Over many years, honey from diferent parts of the world have been shown to be one of the highest potential natural products in which phenolics, lavonoids, ascorbic acids, and some enzymes serve as potent antioxidants [32]. The antioxidant properties of honey are derived from both enzymatic (e.g., catalase, glucose oxidase, and peroxidase) and nonenzymatic substances (e.g., phenolic compounds, ascorbic acid, α-tocopherol, carotenoids, amino acids, proteins, and Maillard reaction products).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Over many years, honey from diferent parts of the world have been shown to be one of the highest potential natural products in which phenolics, lavonoids, ascorbic acids, and some enzymes serve as potent antioxidants [32]. The antioxidant properties of honey are derived from both enzymatic (e.g., catalase, glucose oxidase, and peroxidase) and nonenzymatic substances (e.g., phenolic compounds, ascorbic acid, α-tocopherol, carotenoids, amino acids, proteins, and Maillard reaction products).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…It has been suggested that iodine has a negative impact on cells involved in the wound healing process and because of this its safety and efficacy have been questioned [24]. In contrast, the honey-based product showed excellent cytocompatibility with tissue cell cultures [29] and for long term use as in the management of chronic foot ulcers proved to be efficacious, cost-effective, and acceptable by both clinicians and patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies and bioactivity demonstrate the eiciency of honey in wound healing, maintaining a moist environment, promoting drainage of wound exudate and autolytic debridement [144]. It has been reported in minimizing malodour and scar formation of the wound [145] as well as angiogenic activity [146].…”
Section: Honey Dressingsmentioning
confidence: 99%
“…Van den "erg et al [142] investigated the anti-inlammatory properties of diferent types of honey in vitro by testing reactive oxygen species (ROS) inhibition capability and found "merican buckwheat honey exhibits high ROS inhibition ability. Many clinical studies have been performed on the basis of the antimicrobial efect of honey [143][144][145]. Clinical studies and bioactivity demonstrate the eiciency of honey in wound healing, maintaining a moist environment, promoting drainage of wound exudate and autolytic debridement [144].…”
Section: Honey Dressingsmentioning
confidence: 99%